Boiling and Soaking Methods of Bananas on the Physical and Functional Properties of Banana Flour - Nirmagustina, Dwi Eva (JURNAL AGRIMENT, 2024)
Bananas are a horticultural crop abundant in Lampung Province, Indonesia. Bananas can be made into various products, such as banana flour. The purpose of the research is to determine the effect of boiling and soaking methods of bananas on the physical and functional properties of banana flour. The results showed that there were differences in peeling bananas, slicing bananas, and grinding banana chips between the boiling method and the soaking method on the physical and functional characteristics of banana chips and banana flour, which are color, hardness, water holding capacity (WHC), and oil holding capacity (OHC). The boiling method makes banana skin easy to peel; the banana chips are harder and make it hard to grind; banana chips have a brighter color. The soaking method is easier to slice bananas. Pisang Ambon (banana-type) has higher banana chip hardness than Pisang Janten and Pisang Kepok (plantain-type). The color of banana-type bananas is white, while plantain-type bananas are yellowish white. The boiling method has higher WHC and OHC values than the soaking method. WHC of banana flour with the boiling method ranges from 216.36% to 284.92%, and the soaking method ranges from 128.55% to 148.45%. OHC of banana flour using boiling method 129.04%-145.53% and soaking method 113.86%-123.87%.